(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article under discussion reveals the formation of communicative competence of students in non-linguistic higher educational institutions. The role and aspects of learning English in a technical university based on the concept of competence approach and in the context of multi-disciplinary education had been analyzed. The author considers some methodological principles and peculiarities of teaching a foreign language in a technical university, based on the criteria of professional competence development.